Curtailing Unnecessary Waste Among Operating Room Personnel: Evaluating the Cost Awareness of Commonly Used Surgical Items. Issue 6 (June 2022) - Heiman, Adee J.; Camargo, Lauren; Bhat, Deepa; Desai, Vilok; Patel, Ashit; Ricci, Joseph A.
Background: Operating rooms (ORs) generate 70% of hospital waste, leading to increased costs for the hospital, patient, and the environment. The lack of cost awareness among physicians has been well documented; however, there is little information on anesthesiologists or ancillary OR staff. This study aimed to evaluate the cost awareness of commonly used items at an academic medical center among OR personnel. Methods: Anonymous surveys were distributed to OR personnel (nurses, surgical technicians (STs), nurse anesthetists, anesthesiologists, surgeons, and residents), asking for the estimated costs of ten commonly used items. These costs were then compared against actual costs to evaluate the accuracy of participants' estimates. Responders were clustered by job, highest level of education, and years of experience for comparison. Results: 167 surveys were collected, and overall only 16.4% of estimates were accurate within 50% of actual price. No significant differences in accuracy between groups were identified overall ( P = .2), but both surgical and anesthesia attendings had significantly higher rates of correct responses than their respective residents. No difference was seen in accuracy when all attendings (surgeons and anesthesiologists) were compared with either nurses or STs. Linear regression demonstrated no correlation between number of years at current position or years at institution and number of correct responses ( R 2 = .0025 and R 2 = .005, respectively). Discussion: Addressing the knowledge deficit around item costs via global education of all OR personnel (surgeons, anesthesia providers, and ancillary staff) could be a viable pathway to reduce waste, and thus cost, for our healthcare system.